Impact of large‐loop excision of the transformation zone on cervical morphology: A prospective observational study - Soares, Flávia Zero; Herren, Helmer; Melli, Patrícia Pereira dos Santos; Zaccaro, Marília Veccechi Bijos; Quintana, Silvana Maria (International journal of gynecology and obstetrics, 2025)
To evaluate the impact of large-loop excision of the transformation zone (LLETZ) on cervical dimensions, to identify influencing factors on cervical regeneration and to verify the concordance between ultrasonographic techniques for assessing cervical volume. This was a prospective observational study conducted at the University of São Paulo Clinical Hospital from May 2022 to April 2023. Ultrasonographic measurements of cervical length and volume were obtained before LLETZ and at 3 and 6 months post-procedure. The influence of variables on the regenerative process was evaluated using generalized linear regression models, and the concordance between volume measurements using the cylinder formula and VOCAL (Virtual Organ Computer-Aided Analysis) software was assessed. The mean cervical length decreased from 32.3 mm to 30.3 mm at 3 months but increased to 31.7 mm at 6 months. The volume calculated by the cylinder formula decreased from 15.6 cm to 11.6 cm at 3 months, rising to 12.3 cm at 6 months. Similarly, the volume measured by VOCAL dropped from 16.0 cm to 11.8 cm at 3 months and increased to 13.1 cm at 6 months. The volume of excised tissue influences cervical length, whereas parity affects volume regeneration. Ultrasonography methods for assessing cervical volume showed high concordance. There is a regenerative process of the cervix after LLETZ, complete in terms of length and partial in volume. The volume of the excised tissue and parity influence the regenerative process. Ultrasonographic assessments of cervical volume by two- or three-dimensional methods are comparable.